The textile artist's studio handbook : learn traditional and contemporary techniques for working with fiber, including weaving, knitting, dyeing, painting, and more /: learn traditional and contemporary techniques for working with fiber, including weaving, knitting, dyeing, painting, and more. (2012) - Unknown
No abstract available